A Novel Method for Measurement of Capacitances and Their Loss Factors - Muhammad Taher Abuelma'atti; Hussain Abdullah Alzaher; Sami Saud Buhalim (Active and Passive Electronic Components)
A novel and simple technique for measurement of capacitances and their losses is presented. The method is based on a partially active-R sinusoidal oscillator. Experimental results are in good agreement with the theoretical analysis.